IMPLEMENTASI KEBIJAKAN GERAKAN MASYARAKAT MAGRIB MENGAJI - Harapan Tua, Ganda Ade Saputra, Zaili Rusli, (Jurnal Ilmu Administrasi Negara, 2019)
Policy Implementation of the Magrib Mengaji Community Movement. This studyaims to determine the implementation of the movement of the Koran Maghreb movement inBangkinang District. The research informants consisted of Officials and Staff of the Ministry ofReligion of Kampar Regency, Kesra of Kampar District, Ulama and Community Stores. Data iscollected through interviews, observation and documentation. Data analysis based onphenomenological philosophy that emphasizes verstehen. The results of this study indicate that theimplementation of the community movement policy to study is still there are several problemsincluding low supervision, low community participation. There is no clarity of sanctions for partieswho violate, uneven distribution of the budget. Implementation of Regional Regulations for theMovement of Magriby Community Religion is influenced by several factors, namely the policycontent factor where there is an interest from the target group, the type of benefits, the degree ofchange desired and the location of decision making and the community involved.